Teatr jako narzędzie interwencji politycznej — o Sprawiedliwości Michała Zadary - Dąbrowska, Dorota (Załącznik Kulturoznawczy, 2018)
The article contains an analysis and interpretation of Michał Zadara’s play Sprawiedliwość [Justice] from the point of view of the relation between the performance and the phenomenon of persuasion. The director refers to the events of March ’68 to address the issue of expelling Jews from Poland. His aim is not only to reflect on the meaning of the event and to identify the guilty, but also to provoke legal interventions, to call for justice. This intention is connected with the idea of exceeding the fictional status of a performance in order to use it in social and political reality.